(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Inclusive education is a critical aspect of modern educational systems, aiming to provide equal opportunities for all students, regardless of their physical, intellectual, or social differences. This study investigates the development and implementation of inclusive education in Uzbekistan, exploring its current state, challenges, and opportunities for further improvement. The paper examines key legislative frameworks, such as the Law on Education and the National Strategy for Action on Human Rights, which support the inclusion of students with special needs in general education classrooms. However, the study highlights significant barriers to full implementation, including inadequate teacher training, insufficient infrastructure, limited financial resources, and societal attitudes towards disability. By reviewing national policies and educational practices, this research offers practical recommendations for enhancing inclusive education in Uzbekistan. The paper emphasizes the importance of teacher professional development, public awareness campaigns, and increased financial support for special education to ensure that all students, regardless of their abilities, can access quality education.